Simultaneous determination of As, Cu, Mn, Sb, and Se in drinking water by GRAS with transversely heated graphite atomizer and longitudinal Zeeman-effect background correction - Resta, V. A.; Fernandez, K. G.; de Moraes, M.; Neto, JAG (Perkin-elmer Corp, 2002)
A method has been developed for the direct and simultaneous determination of As, Cu, Mn, Sb, and Se in drinking water by electrothermal atomic absorption spectrometry (ETAAS) using a transversely heated graphite tube atomizer (THGA) with longitudinal Zeeman-effect back- ground correction. The thermal behavior of analytes during the pyrolysis and atomization stages was investigated in 0.028 mol L-1 HNO3, 0.14 mol L-1 HNO3 and 1 + 1 (v/v) diluted water using mixtures of Pd(NO3)(2) + Mg(NO3)(2) as the chemical modifier, With 5 mug Pd + 3 mug Mg as the modifier, the pyrolysis and atomization temperatures of the heating program of the atomizer were fixed at 1400degreesC and 2100degreesC, respectively, and 20 muL of the water sample (sample + 0.28 mol L-1 HNO3, 1 + 1, v/v), dispensed into the graphite tube, analytical curves were established ranging from 5.00 - 50.0 mug L-1 for As, Sb, Se; 10.0 - 100 mug L-1 for Cu; and 20.0 - 200 mug L-1 for Mn. The characteristic masses were around 39 pg As, 17 pg Cu, 60 pg Mn, 43 pg Sb, and 45 pg Se, and the lifetime of the tube was around 500 firings. The limits of detection (LOD) based on integrated absorbance (0.7 mug L-1 As, 0.2 mug L-1 Cu, 0.6 mug L-1 Mn, 0.3 mug L-1 Sb, 0.9 mug L-1 Se) exceeded the requirements of the Brazilian Food Regulations (decree # 310-ANVS from the Health Department), which established the maximum permissible level for As, Cu, Mn, Sb, and Se at 50 mug L-1, 1000 mug L-1, 2000 mug L-1, 5 mug L-1, and 50 mug L-1, respectively. The relative standard deviations (n = 12) were typically < 5.3% for As, < 0.5% for Cu, < 2.1% for Mn, < 11.7% for Sb, and < 9.2% for Se. The recoveries of As, Cu, Mn, Sb, and Se added to the mineral water samples varied from 102-111%, 91-107%, 92-109%, 89-97%, and 101-109%, respectively. Accuracy for the determination of As, Cu, Mu Sb and Se was checked using standard reference materials NIST SRM 1640 - Trace Elements in Natural Water, NIST SRM 1643d - Trace Elements in Water, and 10 mineral water samples. A paired t-test showed that the results were in agreement with the certified values of the standard reference materials at the 95% confidence level.